Blending in heterosyllabic consonant clusters in three Catalan dialects - Recasens, Daniel (ZAS Papers in Linguistics, 2008)
This study is an electropalatographic investigation of clusters composed of /n/ or /l/ followed by the (alveolo)palatal consonants /ʎ, ɲ/ or by dental /t/ in three Catalan dialects, i.e., Majorcan, Valencian and Eastern. Data show that articulatory blending through superposition occurs in the palatalizing environment except when C1 is highly constrained (e.g., dark /l/) or C2 is purely palatal and therefore, produced at a distant articulatory location from C1. Contrary to previous descriptions in the literature, data for /nt, lt/ reveal that blending through superposition rather than assimilation is at work. The implications of these data for theories of speech production are discussed.